2004
DOI: 10.1016/j.femsec.2004.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure in soil chemical and microbiological properties in an upland grassland

Abstract: We characterised the spatial structure of soil microbial communities in an unimproved grazed upland grassland in the Scottish Borders. A range of soil chemical parameters, cultivable microbes, protozoa, nematodes, phospholipid fatty acid (PLFA) profiles, community-level physiological profiles (CLPP), intra-radical arbuscular mycorrhizal community structure, and eubacterial, actinomycete, pseudomonad and ammonia-oxidiser 16S rRNA gene profiles, assessed by denaturing gradient gel electrophoresis (DGGE) were qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
100
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 61 publications
(69 reference statements)
19
100
1
Order By: Relevance
“…The C:N ratio at Site 2 (more recently exposed to fire) was significantly different and higher than at Site 1, probably due to the upward movement of organic compounds caused by the transfer of heat downwards after the fire event (DeBano, 2000). The positive correlations between total N and total organic C contents suggest common microscale variability for these chemical properties (Ritz et al, 2004). High levels of spatial heterogeneity in soil chemical properties were found, confirming what was reported for other ecosystems (Jackson and Caldwell, 1993;Gross et al, 1995;Ritz et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…The C:N ratio at Site 2 (more recently exposed to fire) was significantly different and higher than at Site 1, probably due to the upward movement of organic compounds caused by the transfer of heat downwards after the fire event (DeBano, 2000). The positive correlations between total N and total organic C contents suggest common microscale variability for these chemical properties (Ritz et al, 2004). High levels of spatial heterogeneity in soil chemical properties were found, confirming what was reported for other ecosystems (Jackson and Caldwell, 1993;Gross et al, 1995;Ritz et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Soil pH and N may be spatially autocorrelated up to 5 m (Ettema and Wardle, 2002;Pärtel et al, 2008;Baldrian et al, 2010). Besides the great spatial variability of soil nutrients and pH that is commonly observed in forest soil (Ettema and Wardle, 2002;Štursová and Baldrian, 2011), soil microbial biomass may also be spatially autocorrelated up to 10 m (Ritz et al, 2004), which may affect soil spatial heterogeneity and in turn microbial communities (Lauber et al, 2009). The neighbourhood effect of trees and influence of understorey vegetation were relatively more important in shaping communities of biotrophic fungi rather than freeliving organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the composition of microbial community DNA between replicate soil samples was found to be as great as the variation between treatments in field based studies. The reasons for such variability are not clear, however it is likely that are attributable to the effect of soil chemical attributes plus the contents and composition of organic matter (Clayton et al, 2005;Ritz et al, 2004). According to the authors the DGGE profiling revealed lower number of bands per area in the dry season, but differences in the genetic diversity of bacterial communities along the sequence forest to pasture was better defined than for wet season.…”
Section: Bacteria Diversity Assessed By Pcr-dggementioning
confidence: 99%